The Lithuanian Pop Novel Case: Jurga Ivanauskaitė’s Children of the Moon in the Context of German Popliteratur - Kmita, Rimantas (Literatūra, 2025)
This article analyzes Jurga Ivanauskaitė’s novel Children of the Moon (1988) by applying the theoretical principles of German Popliteratur. Drawing on insights from Moritz Baßler, Carsten Gansel, and other theorists, the study examines four main aesthetic strategies: the poetics of archiving, self-staging (Selbstinszenierung), fixation of the present, and post-adolescent rituals. The analysis reveals that the novel demonstrates essential features of Popliteratur – notably, cataloguing cultural artifacts, constructing identity through performative roles, documenting generational Zeitgeist, and depicting ‘post-adolescent’ rebellion against societal norms. The novel’s characters, suspended between adolescence and adulthood, create alternative initiation rituals, which are often self-destructive in nature. The late Soviet context imbues these strategies with distinctive content: cultural capital replaces consumer culture, while the playful approach to identity transforms into an existential practice of resistance. The article demonstrates that the Popliteratur concept allows for avoiding the dichotomous evaluation characteristic of the traditional Lithuanian criticism and offers a productive analytical approach to Lithuanian popular literature studies.
Keywords: Jurga Ivanauskaitė; Popliteratur; late Soviet period; popular culture; Lithuanian literature